KERUGIAN-KERUGIAN PADA PIPA LURUS DENGAN VARIASI DEBIT ALIRAN - Muchsin, Muchsin (Jurnal MEKANIKAL, 2013)
Fluid flow a pipe (internal flow) always happens losses caused by friction between the wall because of the influence of the fluid’s viscosity. High coefficient of friction affect them directly to a substantial reduction of the pressure and eventually to the amount of energy needed to drain the fluid. Application of this research is on the installation of pipeline taps, pertamina’s crude oli supply, installation of sump drainage pipe in the mining regions and many other applications. In this study, will be varied so that the flow rate will be obtained by varying Reynolds number, and will be searched the relationship betwenReynolds and major losses, the speed of the mayor losses that occur with such a relationship will be obtained as a study in fluid mechanics studies From this study indicate that the relationship between Reynolds number the friction factor is which means the greater the speed of the major losses will be greater. The lowest value of friction factor at full valve opening with Re= 1,91 x 105 to the value f = 1,513 x 10-2 and the highest value of friction factor occurs at the valve opening quarter with Re = 4,30 x 104 to the value f= 2,195 x 10-2. The highest major with the value of ∆h= 196,67 mm at a speed v= 19,572 m/s (at full valve opening), the lowest rate of major losses on the value of ∆h= 0 (small) at the speed of v = 2,453 m/s.